Experimental study of hydraulic characterization of transverse waves induced by vortex shedding in resonance - Kimiya Kamaei; Mehdi Ghomeshi; Seyed Mahmood Kashefipour; Mehdi Daryaee (Ain Shams Engineering Journal, 2023)
This study investigated the effect of obstacle shape on forming four modes of transverse waves in resonance. Cubic (flow collision to the vertex) and cylindrical obstacles were used for this purpose. All experiments were performed in a flume with a length of 16 m, a width of 1.25 m, and a height of 0.6 m. The obstacles were arranged in-line at three transversal distances and staggered at one transversal distance and a constant longitudinal distance. The results confirmed the significant impact of obstacle shape on the formation and characteristics of transverse waves, such as relative amplitude and frequency. In resonance situation, the cubic obstacles showed a higher relative wave amplitude and lower frequency than the cylindrical obstacles. For cubic and cylindrical obstacles, the frequency increased at all transversal distances with increasing the wave number. Hence, the lowest and highest frequencies were observed in wave modes I and IV, respectively. Since the Strouhal number depends on the density of obstacles, its value decreased in the in-line arrangement with decreasing the obstacle density. On average, the cubic obstacles showed a lower Srouhal number than the cylindrical ones for all four wave modes. Using dimensional analysis and the experimental results, some equations were presented in this study to calculate the relative amplitude of transverse waves in resonance with the help of advanced statistical software.